The Role and Function of English Language in ESP Classes - Zokirovna, Salieva Ziroat (International Journal on Integrated Education, 2023)
English is taught to students whose first language is not English but who require it for a specific task, activity, or goal through ESP. The acronym ESP stands for "English for Specific Purposes," also known as "English for Special Purposes." Although it is widely accepted that teaching ESP courses should emphasize language skills such as reading, writing, listening, and speaking, this often depends on the needs and interests of the students. The course design for English for Specific Purposes, the role of the teacher and student in ESP, and difficulties related to the environment, the student, and other factors in ESP teaching are all covered in this article.